Functional trait filtering of aerial insectivorous forest bats in Amazonian cattle-dominated landscapes - Alana Zammit; Rosenwyn Petherick-Davies; Germana Vizzotto Osowski; Márcia I G Zanella; Lais Silva Mariscal Baba; Luana Alves; André Luiz Gama Nogueira; Claudia Almeida Scariot; Adroaldo J. Zanella; Ana Filipa Palmeirim; Harriet Bartlett; Ricardo Rocha (Forest Ecology and Management, 2026)

Second primary cancers among females with a first primary cervical, uterine and ovarian cancer: a population-based study in North Portugal - Elisabete Gonçalves; Filipa Fontes; Jéssica Rocha Rodrigues; Rita Calisto; Maria José Bento; Nuno Lunet; Samantha Morais (Cancer Causes & Control, 2026)

Population Structure of the European Seabass (Dicentrarchus labrax) in the Atlantic Iberian Coastal Waters Inferred from Body Morphometrics and Otolith Shape Analyses - Rafael Gaio Kulzer; Rodolfo Miguel Silva; Ana Filipa Rocha; João Soares Carrola; Rosária Catarino Seabra; Eduardo Rocha; Karim Erzini; Alberto Teodorico Correia (Fishes, 2025)
The European seabass (Dicentrarchus labrax) is one of the most emblematic coastal fish species in the Northeast Atlantic, with high commercial value for fisheries and aquaculture, and importance for sport and recreational fishing. Despite its socio-economic importance, the Iberian divisions, Cantabrian Sea (8c) and the Atlantic Iberian waters (9a), defined by the International Council for the Exploration of the Sea (ICES), lack stock delimitation data. Moreover, this species is missing basic biological information, a seasonal reproductive fishing ban, and the annual landings in this region are more than double the levels recommended by ICES. To investigate the population structure of D. labrax in these areas, 140 adult individuals (36–51 cm of total length) were collected between January and March 2025 in three locations along the Atlantic coast of the Iberian Peninsula: Avilés (n = 47), Peniche (n = 48), and Lagos (n = 45). Fish from each location were analyzed for body geometric morphometrics (truss network) and otolith shape contour (Elliptical Fourier Descriptors). Data were evaluated using univariate and multivariate tests to assess spatial differences and reclassification success among locations. Results revealed regional differences using body morphometry and otolith shape analyses. The overall reclassification success was 68% for truss networking, 51% for otolith shape, and 65% when both methods were combined. Despite the observed differences, the absence of clear, isolated populations supports the ICES definition of a single, though not homogeneous, European seabass stock in the Atlantic Iberian coastal waters. Nevertheless, individuals from Avilés exhibited distinctive morphometric patterns and otolith shapes, suggesting possible adaptations to local selective pressures in slightly different environments. Further studies integrating genetic tools, otolith chemistry, parasitic fauna and telemetry analyses, as well as other fish samples from adjacent areas such as the Bay of Biscay, are recommended to achieve a more comprehensive understanding of the population structure and migration patterns of this key species in the Atlantic Iberian coastal waters.

Lead as an environmental toxicant in models of synucleinopathies - Liana Shvachiy; Ângela Amaro-Leal; Filipa Machado; Isabel Rocha; Vera Geraldes; Tiago F. Outeiro (Chemosphere, 2025)

Diel activity of free-ranging cats and their mammalian and avian prey on the oceanic Madeira Island, Macaronesia - Edie Abrahams; Elena J. Soto; Kane Powell; João Nunes; Ana Filipa Palmeirim; Ricardo Rocha (European Journal of Wildlife Research, 2025)
Species’ activity patterns offer insights into overall behaviour as well as intra- and inter-species interactions. In multiply invaded systems, synergistic interactions between invasive species can contribute to the decline of native fauna. We conducted a protected area-wide camera trap survey to investigate the diel activity patterns of invasive free-ranging cats and their overlap with both native and non-native prey on the Macaronesian island of Madeira, Portugal. Free-ranging cats showed greater temporal overlap with non-native mammalian prey than with native and non-native birds. Specifically, cats exhibited the highest coefficient of temporal overlap with rabbits, followed by rodents, passerines, and lastly partridges. This suggests that non-native prey, including rabbits and partridges (both alien game species in Madeira), may be subsidising cat populations, potentially leading to hyperpredation of native prey. Our results highlight the need for evidence-based management of free-ranging cat populations and a reconsideration of practices associated with the restocking of alien game species.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Diel activity of insectivorous bats in response to land-use change in São Tomé Island, Gulf of Guinea - Ana Catarina Araújo-Fernandes; Ana Sofia Castro-Fernandes; Patrícia Guedes; José Cassari; Vanessa Alves Mata; Natalie Yoh; Ricardo Rocha; Ana Filipa Palmeirim (Biodiversity and Conservation, 2025)

Responses of insectivorous bats to different types of land-use in an endemic-rich island in Central West Africa - Ana Sofia Castro-Fernandes; Ana Catarina Araújo-Fernandes; Patrícia Guedes; José Cassari; Vanessa A. Mata; Natalie Yoh; Ricardo Rocha; Ana Filipa Palmeirim (Biological Conservation, 2025)

Nature-based solutions to increase rice yield: An experimental assessment of the role of birds and bats as agricultural pest suppressors in West Africa - Madalena Sottomayor; Ana Filipa Palmeirim; Christoph F.J. Meyer; Ricardo F. de Lima; Ricardo Rocha; Ana Rainho (Agriculture, Ecosystems & Environment, 2024)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Effects of dietary arachidonic acid on cortisol production and gene expression in stress response in Senegalese sole (Solea senegalensis) post-larvae - Dulce Alves Martins; Filipa Rocha; Filipa Castanheira; Ana Mendes; Pedro Pousão-Ferreira; Narcisa Bandarra; Joana Coutinho; Sofia Morais; Manuel Yúfera; Luís E. C. Conceição; Gonzalo Martínez-Rodríguez (Fish Physiology and Biochemistry, 2013)